Start moving - benefits of an onsite workplace health program in the age of digitalization - Borle Prem; Boerner-Zobel Franziska; Bias Harald; Voelter-Mahlknecht Susanne (Journal of Occupational Medicine and Toxicology, 2021)
Abstract Background The process of digitization should simplify our work and improve related processes (i.e. quality, transparency). Moreover, it enables the home office, which is greatly expanded due to the current pandemic. Regarding workplace health, it should be noted that with increasing digitization, physical activity decreases, and as a result, the number of work-related diseases will increase. On the other hand, increasing digitization also offers promising opportunities for new approaches to workplace health promotion. With these positive as well as negative effects in mind, we designed a workshop to increase physical activity at work. This protocol describes our approach to a live workshop concept. Methods We use a randomized controlled trial with two intervention groups: a live workshop with and without additional reminders. The workshop intervention design consists of a baseline measurement, two workshops, and one follow-up measurement. Each workshop takes place in small groups (n < 11). We use a randomized allocation to both groups. To control for health-related effects and the expected behavior change we examine (i) physical activity (i.e. active time, taken steps, etc.) by a tracking device (ii) physical wellbeing, motivation, and volition by an online questionnaire, and (iii) participants also report physical activity by a diary. All measurements are taken one week before the respective workshop and 24 weeks after the initial baseline measures. Discussion A live workshop offers advantages such as very personal interactions and a low technical effort. However, during the current pandemic, there are some limitations (i.e. small groups, pay attention to hygienic guidelines). Based on the upcoming experiences of this workshop, a web-based approach might offer some advantages (i.e. easier daily implementation, independent from a participant’s location) regarding home office workplaces and the increasing digitization. On the other hand, there are also mandatory requirements as a stable internet connection and technical equipment (i.e. webcam, microphone). Overall, a step by step development of a web-based workshop, based on the experience of the live workshop, can be regarded as advantageous. Trial registration Since this article reports a health promotion intervention concept with human participants, we registered it in the German Clinical Trials Register (DRKS). Number: DRKS00021512 , Date:30.10.2020.